Pengaruh Brand Equity, Brand Trust, Brand Engagement terhadap Customer Loyalty Bank Tabungan Negara Kcs Jakarta Harmoni Dimediasi oleh Customer Satisfaction - Astuti, Nurul; Yokie Radnan Kristiyono (IPM2KPE, 2025)
This study aims to analyze the influence of brand equity, brand trust, and brand engagement on customer loyalty, with customer satisfaction as a mediating variable. This study was conducted on mortgage customers at PT Bank Tabungan Negara (Persero), Tbk's Harmoni Sharia Branch Office in Jakarta. A quantitative approach was used with a purposive sampling technique for 100 respondents. Data were analyzed using the Partial Least Squares Structural Equation Modeling (PLS-SEM) method with the assistance of SmartPLS software. The results indicate that brand equity and brand trust have a significant influence on customer satisfaction, while brand engagement has no direct effect. In the context of customer loyalty, only brand engagement and customer satisfaction have been shown to have a significant direct influence, while brand equity and brand trust have no significant direct effect. These findings confirm the central role of customer satisfaction in shaping loyalty and highlight the importance of improving the quality of the customer experience through service, transparency, and emotional interaction with the brand. Therefore, brand management strategies in Islamic banking need to focus on creating meaningful value to maintain and enhance customer loyalty sustainably. Keywords: Brand Equity, Brand Trust, Brand Engagement, Customer Satisfaction